2024 Election Delay Instructions Democracy Climate - Junaedi, Junaedi (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The 1945 Constitution imposes stringent constraints on the President's authority, confining their tenure to a duration of precisely five years, with the possibility of extension for an additional period not exceeding ten years. In Indonesia, elections are conducted at intervals of five years, allowing for a single occurrence within this time frame. In the event that the 2024 elections are postponed and the presidential term is extended for three periods, it is likely to have a detrimental impact on the democratic climate and raise concerns regarding the violation of the country's constitution. Such actions could be characterized as a form of institutional terrorism.